Incidence of mycosis fungoides and Sézary syndrome in the Netherlands in the last two decades. (October 2021) - Ottevanger, Rosanne; de Bruin, Digna; Willemze, Rein; Jansen, Patty; Bekkenk, Marcel; de Haas, Ellen; Horvath, Barbara; van Rossum, Michelle; Sanders, Cornelus; Veraart, Joep; Vermeer, Maarten; Quint, Koen
Abstract : Cutaneous T-cell lymphomas (CTCLs) are a heterogeneous group of non-Hodgkin lymphomas that differ greatly in clinical presentation and prognosis. Mycosis fungoides (MF) is the most frequent subtype. Sézary syndrome (SS) is less prevalent but has a much more unfavourable prognosis. Previous studies have shown that the incidence of CTCL has tripled between 1970 and 2000 but since then has stabilized. However, data on the incidence of MF and SS in the Netherlands have never been published. The aim of the present study was to estimate the changes in incidence of newly diagnosed MF and SS in the Netherlands over the last 20 years. Annual incidence rates were retrieved from the Dutch Cutaneous Lymphoma Registry (DCLR) between January 2000 and December 2019. In all cases, the diagnosis was based on the clinicopathological criteria of the World Health Organization European Organisation for Research and Treatment of Cancer classification and confirmed by an expert panel of dermatologists and pathologists at a periodical meeting of the Dutch Cutaneous Lymphoma Working Group. We calculated the number of registered patients with MF and SS per 100 000 persons, corrected for the size of the Dutch population. 1044 patients with MF, including 238 patients with folliculotropic MF (FMF), and 93 patients with SS were included. In 2000, the corrected number of cases of MF was 0.19 per 100 000 persons, while this was 0.35 per 100 000 in 2010 and 0.46 per 100 000 persons in 2019. This means that a 2.42-fold increase, corrected for Dutch population growth, was seen between 2000 and 2019 for the incidence of MF in the Netherlands. In 2000, 2010 and 2019 the corrected incidences for SS were 0.013, 0.018 and 0.075 per 100 000 persons, respectively. The overall increase for SS was 6.0-fold corrected for the Dutch population between 2000 and 2019. In summary, a significant increase of patients with classical MF, FMF and SS included in the DCLR was seen over the past 20 years. In contrast to previous studies that suggest a stabilization since 2000, this study shows that the incidence of patients with MF and SS in the Netherlands increased 2.42-fold over the past two decades.